2017
DOI: 10.5056/jnm16171
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of the Endolumenal Functional Lumen Imaging Probe in Gastrointestinal Motility Disorders

Abstract: Gastrointestinal sphincters play a vital role in gut function and motility by separating the gut into functional segments. Traditionally, function of sphincters including the esophagogastric junction is studied using endoscopy and manometry. However, due to its dynamic biomechanical properties, data on distensibility and compliance may provide a more accurate representation of the sphincter function. The endolumenal functional lumen imaging probe (EndoFLIP) system uses a multi-detector impedance planimetry sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…Intraoperative distensibility measurement using FLIP was first reported by Perretta et al Subsequent studies further confirmed that the CSA of the EGJ and the LES‐DI significantly increased after a Heller myotomy or POEM . Measuring distensibility with FLIP intraoperatively offers the possibility to assess the efficacy of LES myotomy in real time, which potentially predicts a patient's clinical response to therapy . Ata‐Lawenko et al proposed that a cut‐off value of distensibility ≤1 mm 2 /mmHg and that of a diameter ≤5 mm indicated a need for dilatation, myotomy or POEM .…”
Section: Flip For Achalasiamentioning
confidence: 99%
See 4 more Smart Citations
“…Intraoperative distensibility measurement using FLIP was first reported by Perretta et al Subsequent studies further confirmed that the CSA of the EGJ and the LES‐DI significantly increased after a Heller myotomy or POEM . Measuring distensibility with FLIP intraoperatively offers the possibility to assess the efficacy of LES myotomy in real time, which potentially predicts a patient's clinical response to therapy . Ata‐Lawenko et al proposed that a cut‐off value of distensibility ≤1 mm 2 /mmHg and that of a diameter ≤5 mm indicated a need for dilatation, myotomy or POEM .…”
Section: Flip For Achalasiamentioning
confidence: 99%
“…Gourcerol et al found that fasting pyloric compliance decreased in a subgroup of patients with gastroparesis, and dilatation in these individuals improved their quality of life scores . Ata‐Lawenko et al proposed that the cut‐off value of distensibility for intervention should be <10 mm 2 /mmHg …”
Section: Flip For Pylorus and Gastroparesismentioning
confidence: 99%
See 3 more Smart Citations